Exposed bone in patients with head and neck cancer treated with radiation therapy: An analysis of the Observational Study of Dental Outcomes in Head and Neck Cancer Patients (OraRad). Issue 3 (19th October 2021) - Treister, Nathaniel S.; Brennan, Michael T.; Sollecito, Thomas P.; Schmidt, Brian L.; Patton, Lauren L.; Mitchell, Rebecca; Haddad, Robert I.; Tishler, Roy B.; Lin, Alexander; Shadick, Ryann; Hodges, James S.; Lalla, Rajesh V.
Abstract : Background: Patients with head and neck cancer (HNC) treated with radiation therapy (RT) are at risk for jaw osteoradionecrosis (ORN), which is largely characterized by the presence of exposed necrotic bone. This report describes the incidence and clinical course of and risk factors for exposed intraoral bone in the multicenter Observational Study of Dental Outcomes in Head and Neck Cancer Patients (OraRad) cohort. Methods: Participants were evaluated before RT and at 6, 12, 18, and 24 months after RT. Exposed bone was characterized by location, sequestrum formation, and other associated features. The radiation dose to the affected area was determined, and the history of treatment for exposed bone was recorded. Results: The study enrolled 572 participants; 35 (6.1%) were diagnosed with incident exposed bone at 6 (47% of reports), 12 (24%), 18 (20%), and 24 months (8%), with 60% being sequestrum and with 7 cases (20%) persisting for >6 months. The average maximum RT dose to the affected area of exposed bone was 5456 cGy (SD, 1768 cGy); the most frequent associated primary RT sites were the oropharynx (42.9%) and oral cavity (31.4%), and 76% of episodes occurred in the mandible. The diagnosis of ORN was confirmed in 18 participants for an incidence rate of 3.1% (18 of 572). Risk factors included pre‐RT extractions ( P = .008), a higher RT dose ( P = .039), and tobacco use ( P = .048). Conclusions: The 2‐year incidence of exposed bone in the OraRad cohort was 6.1%; the incidence of confirmed ORN was 3.1%. Exposed bone after RT for HNC is relatively uncommon and, in most cases, is a short‐term complication, not a recurring or persistent one. Abstract : The 2‐year incidence of exposed bone in the Observational Study of Dental Outcomes in Head and Neck Cancer Patients cohort is 6.1%, and the incidence of confirmed cases of jaw osteoradionecrosis is 3.1%. Exposed bone after radiation therapy for head and neck cancer is relatively uncommon and, in most cases, is a short‐term complication, not a recurring or persistent one.